Addressing the Mental Health Needs of Youth in Times of Crisis: A Study on Job and Financial Insecurity Post-COVID-19 (London Journal of Research In Management & Business, 2024)
The COVID-19 pandemic has had a significant impact on various aspects of social and economic life. One area that has been particularly affected is the mental health of young people. This study aims to investigate the factors that contribute to mental illness in youth in the post-COVID-19 pandemic period. A sample of 300 youths participated in the study by completing a questionnaire that was developed based on the YoungMinds Malaysia initiative. The questionnaire explored the perceptions of young people on various factors that can contribute to mental illness, including job and financial concerns. The study findings shed light on the unique mental health perceptions of youth in comparison to other age groups. The study highlights the need for targeted intervention strategies to address the mental health issues faced by youth, particularly in the areas of job and financial insecurity. The findings have significant implications for policymakers and mental health professionals in Malaysia and beyond.
Keywords: COVID-19; Pandemic; Malaysia; Youth